The THO/TREX Complex Active in Alternative Splicing Mediates Plant Responses to Salicylic Acid and Jasmonic Acid - Nengxu Sun (MDPI AG, 2021)
Salicylic acid (SA) and jasmonic acid (JA) are essential plant immune hormones, which could induce plant resistance to multiple pathogens. However, whether common components are employed by both SA and JA to induce defense is largely unknown. In this study, we found that the enhanced disease susceptibility 8 (EDS8) mutant was compromised in plant defenses to hemibiotrophic pathogen Pseudomonas syringae pv. maculicola ES4326 and necrotrophic pathogen Botrytis cinerea, and was deficient in plant responses to both SA and JA. The EDS8 was identified to be THO1, which encodes a subunit of the THO/TREX complex, by using mapping-by-sequencing. To check whether the EDS8 itself or the THO/TREX complex mediates SA and JA signaling, the mutant of another subunit of the THO/TREX complex, THO3, was tested. THO3 mutation reduced both SA and JA induced defenses, indicating that the THO/TREX complex is critical for plant responses to these two hormones. We further proved that the THO/TREX interacting protein SERRATE, a factor regulating alternative splicing (AS), was involved in plant responses to SA and JA. Thus, the AS events in the eds8 mutant after SA or JA treatment were determined, and we found that the SA and JA induced different alternative splicing events were majorly modulated by EDS8. In summary, our study proves that the THO/TREX complex active in AS is involved in both SA and JA induced plant defenses.